Efektivitas Pendidikan Kesehatan Menggunakan Media Leaflet Dan Penyuluhan Individual Terhadap Pengetahuan Pencegahan Kekambuhan Asma - Setiyarini, Tatik; , Abi Muhlisin, SKM, M.Kep; , Endang Zulaicha, S.Kp (2016)
Asthma is an inflammatory disease of the respiratory system. Recurrence of asthma can be triggered by several factors such as the environment, food, cold air, and emotions. Increased asthma sufferers due to lack of knowledge of how to prevent asthma relapse neighbor. Increased knowledge about the prevention of recurrence of asthma can be done by health counseling. Health education can be done by providing leaflets and individual counseling. This study aims to determine the effectiveness of health education using leaflets media and individual counseling on the prevention of recurrence of asthma knowledge. Researchers used quantitative research with pre experiment design and static design group comparasion. The population in this penelitiaan is asthmatic patients who seek treatment at the Polyclinic RSP dr. Ario Wirawan Salatiga with a sample of 40 respondents were divided into two groups by using consecutive sampling technique. The results showed that the method is more effective than individual education by providing media leaflets (0.00 <0.01). Expected of respondents who have sufficient knowledge and less able to improve their knowledge by seeking information from a variety of sources of information, while the hospital is expected to choose an effective method of implementing health promotion. Keywords: Health education, knowledge, leaflets, individual counseling